A quality improvement project to improve the effectiveness and patient-centredness of management of people with mild-to-moderate kidney disease in primary care. Issue 1 (29th April 2014) - Thomas, Nicola; Gallagher, Hugh; Jain, Neerja
Abstract: Chronic kidney disease (CKD) stages 3 to 5, affects 6-7% of the adult population and is an important risk factor for both advanced kidney disease and cardiovascular disease. This paper describes a quality improvement project that aimed to establish consistent implementation of best practice in people with stage 3-5 kidney disease who were managed in primary care. The intervention was a Care Bundle for CKD. The bundle included three evidence-based, high impact interventions based on National Institute for Care Excellence (NICE, 2008) guidance, with an additional and novel self-management element. 29 GP Practices in England and Wales began the study. They undertook training in clinical management of CKD and in facilitation of self-management, with the self-management content designed and led by patients. Practices were asked to report baseline and then monthly outcome data extracted from practice computer systems. The project team provided implementation and ongoing quality improvement support for participating Practices. Ten Practices dropped out of the study following the training. Data submissions were incomplete in six Practices who continued to apply the care bundle. At the project end, a decision was taken by the study team to perform the final analysis on those thirteen Practices which completed the project and submitted at least six sets of monthly Practice-level outcome data. In these Practices the Care Bundle was applied to under 20% of the registered CKD stage 3 to 5 population in 5 Practices, 20-29% in 3 Practices, 30-49% in 2 Practices and ≥50% in 3 Practices (998 patients in total). Of these, 671 patients (75%) agreed to the self-management component of the intervention. The reliability (at project end) in those who received the Bundle was 100%. The Bundle was applied to an additional 315 patients in the six Practices who completed the project but did not submit regular practice-level monthly data. In the thirteen remaining Practices, the achievement of NICE (2008) blood pressure targets at the start of the project was 74.8% in people with CKD stage 3-5 and no diabetes and 48% in people with CKD stage 3-5 and diabetes. At the project end these figures in the same Practices were 76.7% and 49.2% respectively. These improvements were achieved in spite of Practices increasing their recording of prevalence rate (that is, identifying and recording more patients with CKD on the Practice CKD Register). In conclusion, a care bundle can be implemented in primary care. However, maintaining engagement with primary care health care professionals and maximising exposure to an intervention in patients seen infrequently are significant challenges to generalisation and sustainability.